Wind turbine placement and externalities - Patrick Hoffmann; Mathias Mier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
We apply Open Street Map to identify available placement cells and Global Wind Atlas to determine average wind speeds on a 500 x 500m grid in Germany (1.3 million cells). Minimum distances to obstacles such a roads and buildings leave 535,000 potential placement cells. We calculate distance-dependent noise and visibility damages for each placement cell by using property prices for each of the 401 German counties. We mini- mize the sum of externalities and project cost given a certain expansion target of aver- age power output, thereby allowing to build two different turbine types. The externality share is 13% for the first 3,600 turbines and 52% with total damages of 293 billion e when installing 83,000 turbines (349 GW rated power). The externality share grows up to 311% with total damages of 1,409 billion e when not considering externalities in the placement process.
Keywords: C61; H23; Q52; R14; 330; wind turbine; placement; property prices; externality; noise; visibility